Effect of Sweetness Level and Amino Acid Composition of Palm Sugar on Feed Intake of Trichoglossus haematodus in Captivity - Siti Nuramaliati Prijono; Rini Rachmatika (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2020)
Palm sugar solution diets that were offered to the Lorikeets contain high energy, low protein and rich in amino acids similar to nectar. The major components of palm sugar are sucrose, which has a sweet taste. The Lorikeets can detect energy-rich from the sweet taste of the feed. The aim of the study was to determine the influence of sweetness level and amino acid composition in palm sugar solution diets on feed intake of T. haematodus. The research method was completely randomized design arranged in a factorial with two factors. The first factor consisted of 4 types of palm sugars, i.e. aren, coconut, siwalan/palmyra, and nipah sugar with a different degree Brix in 13.5º, 14.0º, 14.5º, and 15.0º Brix.While the second factor consisted of two treatments, with and without the addition of the commercial baby biscuit. The results showed that the feed intake of Siwalan sugar was significantly higher than the other palm sugar solution diets. Siwalan sugar solution diet has high sweetness level, sucrose content and essential amino acid Lysine. This study provides the new information regarding the sweetness level of palm sugar and amino acid composition in the diet that can affect feed intake of T. haematodus. Therefore, this information will help to make a formulation of appropriate diet that meets the nutrient requirements especially amino acid for the birds.